Indonesian Tourism Village Potentials, Marketing Strategies And Language: A Case of Wringinsongo Village - Agustina, Hiqma Nur; Anyassari, Nugrahaningtyas Fatma; Fauzia, Maya Rizki (Modality Journal: International Journal of Linguistics and Literature, 2024)
Realizing that each human being is naturally gifted with numerous talents, the objective of the study is to identify the potentials of Wringinsongo village and the marketing strategies the village has implemented to realize a tourism village. Wringinsongo village has abundant natural and human resources waiting to be explored, namely Sumberingin swimming pond, multipurpose building, natural clean water source, and local products such as traditional drinks made from turmeric, banana and papaya chips, as well as Jemblem, a traditional snack made from fried cassava. This study employed a descriptive qualitative design. The data collection methods were in-depth interviews, observations, and documentation. The findings revealed that due to some changes in management, the BUMDes has yet to be able to apply optimal marketing strategies. Furthermore, the village did not have any promotional videos or social media. The marketing strategies using a language approach were used to spread information about Wringinsongo village and its potential. It is expected that the village management will implement marketing strategies that use a language approach more frequently to support the development of Wringinsongo village into a tourism village. The marketing strategy using a language approach is to use attractive captions containing information about the facilities, infrastructure, and various potentials of Wringinsongo Village. Abstrak Menyadari bahwa setiap manusia secara alami memiliki berbagai bakat, penelitian ini bertujuan untuk mengidentifikasi potensi Desa Wringinsongo dan strategi pemasaran desa yang telah diterapkan untuk mewujudkan desa wisata. Desa Wringinsogo memiliki sumber daya alam dan manusia yang melimpah untuk dijelajahi, yaitu kolam renang Sumberingin, gedung serbaguna, sumber air bersih alami, dan produk lokal seperti minuman tradisional yang terbuat dari kunyit, pisang dan keripik pepaya serta Jemblem, camilan tradisional yang terbuat dari singkong goreng. Penelitian ini menggunakan desain deskriptif kualitatif. Metode pengumpulan data adalah wawancara mendalam, observasi, dan dokumentasi. Temuan mengungkapkan sehubungan dengan beberapa perubahan dalam manajemen, BUMDes belum dapat menerapkan strategi pemasaran yang optimal. Selain itu, desa tidak memiliki video promosi atau media sosial, strategi pemasaran menggunakan pendekatan bahasa, untuk menyebarkan informasi tentang desa Wringinsongo dan potensinya. Diharapkan manajemen desa dapat menerapkan strategi pemasaran yang menggunakan pendekatan bahasa lebih sering untuk mendukung pengembangan Desa Wringinsongo menjadi desa wisata. Strategi pemasaran menggunakan pendekatan Bahasa adalah dengan menggunakan caption yang menarik berisi informasi tentang sarana, prasarana dan berbagai potensi yang dimiliki oleh Desa Wringinsongo.